Non-linear enhancement of ultrafast X-ray diffraction through transient resonances - Stephan Kuschel; Phay J. Ho; Andre Al Haddad; Felix F. Zimmermann; Leonie Flueckiger; Matthew R. Ware; Joseph Duris; James P. MacArthur; Alberto Lutman; Ming-Fu Lin; Xiang Li; Kazutaka Nakahara; et al. (Nature Communications)
Abstract Diffraction-before-destruction imaging with ultrashort X-ray pulses can visualize non-equilibrium processes, such as chemical reactions, with sub-femtosecond precision in the native environment. Here, a nanospecimen diffracts a single X-ray flash before it disintegrates. The sample structure can be reconstructed from the coherent diffraction image (CDI). State-of-the-art X-ray snapshots lack high spatial resolution because of weak diffraction signal. Bleaching effects from photo-ionization significantly restrain image brightness scaling. We find that non-linear transient ion resonances can overcome this barrier if X-ray laser pulses are shorter than in most experiments. We compared snapshots from individual  ≈ 100 nm Xe nanoparticles as a function of pulse duration and incoming X-ray fluence. Our experimental results and Monte Carlo simulations suggest that transient resonances can increase ionic scattering cross sections significantly beyond literature values. This provides a novel avenue towards substantial improvement of the spatial resolution in CDI in combination with sub-femtosecond temporal precision at the nanoscale.